EFFECT OF DEFICIT IRRIGATION ON GROWTH AND YIELD OF OKRO ( ABELMOSCUS ESCULENTUS) (Journal of Science and Technology, 2016)
The study was conducted to determine the effect of deficit irrigation on the growth and yield of the Dwarf Green Long Pod variety of okro (Abelmoschus esculentus). The location of the study was the School of Agriculture Research and Teaching farm of the University of Cape Coast, Cape Coast. Experimental design adopted for the study was the Randomised Complete Block Design and there were four (4) treatments which were replicated three times. Treatments one, two, three and four were the application of 100%, 80%, 70% and 60% of the amount of water lost through evapotranspiration respectively. A daily irrigation water application was used. The study was conducted throughout the four growth stages of okro. The leaf area, number of pods per plant, pod weight, pod length and pod circumference were all measured at the various growth stages.  Soil samples from the various treatment plots were analysed before and after 60 days of planting to determine the amount of nitrogen, phosphorus and potassium (N, P, and K). Similarly, moisture contents were determined before planting, at the developmental and mid stage of growth.  It was observed that treatment two which was the 80% application of ETc per- formed better than the others. It was also observed that the 60% application of ET C gave the poorest results. It can be concluded that irrigating with 80% of estimated water requirement, is the best application for okro.